2006
DOI: 10.1186/ar1911
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: We analyzed the activation and function of dendritic cells (DCs) in the spleens of diseased, lupus-prone NZM2410 and NZB-W/ F1 mice and age-matched BALB/c and C57BL/6 control mice. Lupus DCs showed an altered ex vivo costimulatory profile, with a significant increase in the expression of CD40, decreased expression of CD80 and CD54, and normal expression of CD86. DCs from young lupus-prone NZM2410 mice, before the development of the disease, expressed normal levels of CD80 and CD86 but already overexpressed C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 38 publications
(13 citation statements)
references
References 42 publications
0
13
0
Order By: Relevance
“…To determine the effect of ERα deficiency on the activation state of DCs in NZM mice, we measured the frequency of pDCs and non-pDC CD11c + cells expressing two described markers of DC activation: major histocompatibility complex class II (MHCII), which is required for antigen presentation and CD40, which is necessary for T cell activation (24, 25). Additionally, in Sle 1,2,3 mice, cDCs have increased CD40 expression prior to disease (28). By taking all CD11c + cells, we have some contamination with monocytes, macrophages, and natural killer (NK) cells, however, cDC expression of MHCII is increased in lupus, a traditional marker of cDCs (26, 27).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…To determine the effect of ERα deficiency on the activation state of DCs in NZM mice, we measured the frequency of pDCs and non-pDC CD11c + cells expressing two described markers of DC activation: major histocompatibility complex class II (MHCII), which is required for antigen presentation and CD40, which is necessary for T cell activation (24, 25). Additionally, in Sle 1,2,3 mice, cDCs have increased CD40 expression prior to disease (28). By taking all CD11c + cells, we have some contamination with monocytes, macrophages, and natural killer (NK) cells, however, cDC expression of MHCII is increased in lupus, a traditional marker of cDCs (26, 27).…”
Section: Resultsmentioning
confidence: 99%
“…DCs from lupus patients and lupus prone mice have altered expression of activation markers (27, 28, 32). Furthermore, ERα signaling alters DC activation in response to i n vitro stimulation.…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, uncontrolled DC functions are sufficient to prime for autoimmune reactions. In many experimental models of autoimmunity, DCs accumulate in the secondary lymphoid organs and in the tissues targeted by the autoimmune process (Rosmalen et al, 2000; Kalled et al, 2001; Adachi et al, 2002; Colonna et al, 2006), although the causative mechanism for this accumulation remains unclear. Further support comes from studies demonstrating that the uptake of autoantibody-opsonized apoptotic cells increases DC presentation of self Ags in an inflammatory context (Frisoni et al, 2005).…”
Section: Dendritic Cells In Autoimmunitymentioning
confidence: 99%
“…We found that Sle1,2,3 mice express an Interferon Signature in vivo before the onset of the disease, compared to gender- and age-matched non autoimmune C57BL/6 (B6) mice. To determine the original cellular source of this IFN response, we investigated the dendritic cells (DCs) because of their pivotal role in lupus (55, 56), in which they are abnormally activated (57) and are able to induce autoimmunity (58), and also their ability to activate upon Type I IFNs (3) and produce large amounts of IFNa/b (59). We investigated the expression of Type I IFNs and IFN responsive genes in Sle1,2,3 bone marrow-derived myeloid DCs (mDCs) and plasmacytoid DCs (pDCs) in young pre-diseased mice, in absence of autoantibodies, and we measured Sle1,2,3 BMDCs’ response to stimulation with IFNa and TLR7 and TLR9 agonists and inhibitors.…”
Section: Introductionmentioning
confidence: 99%